Primary Epithelioid Sarcoma of Orbit: A Case Report and Review of the Literature - Erin A. Kaya; Talmage J. Broadbent; Cheddhi J. Thomas; Aaron E. Wagner; Steve H. Thatcher; Wayne T. Lamoreaux; Robert K. Fairbanks; Christopher M. Lee (Case Reports in Oncological Medicine)
Epithelioid sarcoma is a rare high-grade malignancy identified by Enzinger in 1970. It accounts for 1% of all reported soft tissue sarcomas and presents most commonly in distal upper extremities in young adults with a male predominance. At this time, there are only 5 previously reported cases of primary epithelioid sarcoma of the orbit. We present a primary orbital epithelioid sarcoma case of a patient who underwent orbital exenteration followed by external beam radiation treatment. Because the literature is limited, this is to our knowledge the largest descriptive analysis of cases of orbital epithelioid sarcoma. We also provide a detailed review of all the previously reported primary orbital epithelioid sarcoma cases, as well as a discussion on the use of postoperative radiation therapy for patients with epithelioid sarcoma. Surgical resection followed by adjuvant radiation therapy appears to be a safe option for local treatment of this rare malignancy, but further future studies are needed of this rare clinical situation in order to better understand and optimize treatment for patients with orbital epithelioid sarcoma.